The Use of the Saccadometer to Identify Saccadic Characteristics in Myasthenia Gravis: A Pilot Study. Issue 1 (22nd March 2022) - Murray, Craig; Newsham, David; Rowe, Fiona; Noonan, Carmel; Marsh, Ian B.
Abstract : Background: Myasthenia gravis (MG) often presents with ocular signs that mimic other forms of ocular defects, such as isolated cranial nerve palsy. Normal velocity or even hyperfast saccadic eye movements in the presence of deficits of smooth pursuit have been well described in the literature in myasthenic patients. The reason for these paradoxical clinical findings has been reported to be due to increased postsynaptic folding of the fast-twitch fibers responsible for the execution of a saccade which is absent in those fibers responsible for slower, smooth eye movement. Saccadic characteristics therefore offer a point of differential diagnosis between patients suspected of having ocular motility deficits as a result of MG and those caused by other neuropathies. The advent of portable quantitative saccadic assessment means that previously laboratory-based assessments that require specialist equipment and training may now be undertaken clinically, providing a noninvasive test that can aid the differential diagnosis of the condition. The aim of this pilot study was to investigate the feasibility of the saccadometer (Ober Consulting, Poznan, Poland) in detecting the saccadic characteristics associated with myasthenia, specifically normal peak velocity (PV) in a group of patients confirmed with myasthenia. Methods: A group of 5 patients with a confirmed diagnosis of MG were recruited from a single site into the study along with 5 age-matched healthy volunteers. All myasthenic patients had ocular signs such as underaction or limitations of motility confirmed through ocular clinical examination. Healthy volunteers were screened for any underlying ocular motility or neurological defects before inclusion within the study. All participants undertook 100 trials of both 10 and 20° amplitude saccades, and mean PV, amplitude, and latency were recorded using the saccadometer for each individual. Overall, mean PV, amplitude, and latency were collated for both myasthenic and healthy control groups for each saccade size and compared. Results: The mean PV was significantly greater (481 ± 103.5 deg/seconds) for myasthenic patients compared with healthy controls (384 ± 42.8 deg/seconds) ( P < 0.05) in 10° saccades. PV was also greater in myasthenics for 20° saccades; however, this difference did not reach statistical significance for patients with MG (547 ± 89.8 deg/seconds vs 477 ± 104.5 deg/seconds) ( P = 0.14). The latency of participants with MG was not significantly different from those of age-matched healthy participants in 10° saccades but was significantly different for 20° saccades. There was no difference in amplitude measured between the groups. Conclusions: PV for both 10 and 20° saccades was greater in myasthenic patients compared with healthy controls. All myasthenic patients produced normal velocity saccades in the presence of deficits of smooth ocular motility. The results from this small pilot study demonstrate the potential use of the saccadometer in a clinical setting to provide a noninvasive aid in the diagnosis of patients suspected with myasthenia.